Microstructure characterization and biocompatibility behaviour of TiNbZr alloy fabricated by powder metallurgy - Kaya, Mehmet; Yakuphanoğlu, Fahrettin; Elibol, Ebru; Kom, Mustafa (Iop Publishing Ltd, 2019)
The purpose of this study is to produce Ti-10Nb-10Zr orthopaedic implant material by adding non-toxic niobium (Nb) and zirconium (Zr) elemental powders into titanium (Ti) powder. In addition, to compare the microstructure, corrosion and biocompatibility properties of the orthopaedic implant produced with those of porous pure Ti produced similarly. Ti-at%10Nb-at%10Zr and pure Ti materials were produced with traditional sintering by using raw metal powders. The microstructures of the materials were investigated with SEM and XRD studies, corrosion properties using electrochemical corrosion test and biocompatibility behaviours in vivo using rats were examined. Commercially pure titanium (cpTi) has ? phase at room temperature and causes stress shielding, which results in bone loss when used as an orthopaedic implant. ? phase structure in the microstructure of the alloy is formed by the addition of Nb into Ti, and it is hoped that this structure will better adapt to the bone structure. Because the ? structure is more flexible than pure titanium with ? phase. In addition, the increase of the corrosion resistance of the alloy formed with addition of Nb and Zr indicates that the alloy will remain long lasting biocompatible within the body.
Keywords: biocompatibility; TiNbZr; powder metallurgy; microstructure